2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC) 2015
DOI: 10.1109/pvsc.2015.7355750
|View full text |Cite
|
Sign up to set email alerts
|

High quality tunneling oxides for passivated contacts and heterojunctions for high efficiency silicon solar cells

Abstract: We analyze the chemical passivation quality of silicon oxide-nanolayers on crystalline silicon wafers prepared by different oxidation methods with surface photo voltage and quasisteady-state photo conductance measurements. It is shown that for wet chemical oxidation and plasma oxidation, adequate passivation of the interface defects is achieved by subsequent anneal in forming gas environment. Furthermore, we present a simple oxidation method by means of rapid thermal oxidation, which requires no complex surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…Generally, an ultrathin silicon oxide (1-2 nm) formed on silicon surfaces can reduce the D it to the order of 10 12 cm À2 .eV À1 . 34,35 We found that the electron barrier height decreases to 0.29 eV with a D it of 7 3 10 12 cm À2 .eV À1 . This result is consistent with the phenomenon we observed (as shown in Figure 2) where inserting thin SiO 2 reduces the r c at the TiN/SiO 2 /n-Si interface.…”
Section: Electrical Properties Of Tin Film Deposited By Reactive Sputteringmentioning
confidence: 80%
“…Generally, an ultrathin silicon oxide (1-2 nm) formed on silicon surfaces can reduce the D it to the order of 10 12 cm À2 .eV À1 . 34,35 We found that the electron barrier height decreases to 0.29 eV with a D it of 7 3 10 12 cm À2 .eV À1 . This result is consistent with the phenomenon we observed (as shown in Figure 2) where inserting thin SiO 2 reduces the r c at the TiN/SiO 2 /n-Si interface.…”
Section: Electrical Properties Of Tin Film Deposited By Reactive Sputteringmentioning
confidence: 80%
“…K.M. Gad и соавторы в работе [8] сравнили пассивирующие свойства пленок SiO 2 , выращенных различными методами. Как показали результаты, ультратонкие пленки диоксида кремния, синтезированные методом быстрого термического отжига, показали наилучшие свойства, в особенности после отжига в формирующем газе N 2 (95%) + Н 2 (5%) при температуре 400 о С в течение 20 минут.…”
Section: Introductionunclassified
“…This topic has thus been the object of a large amount of fundamental 2 and applied investigations 3 . It is still impacting various research fields targeting both applied and fundamental physics in which flexible opto-electronic devices 4,5,6 , sensors 7,8 or biological functions are still feeding new paradigms 9,10 .…”
Section: Introductionmentioning
confidence: 99%